Managing Information Security Breaches : Studies from Real Life. - Krausz, Michael (IT Governance Pub., 2010)
This book provides a general discussion of, and a source of learning about, what information security breaches are, how they can be treated and what ISO27001 can offer in that regard, spiced with a number of real-life stories of information security incidents and breaches. It is a 'first line of defence' for the reader who is affected by an incident and wants to turn to a source of guidance and direction.